Математична та інформаційна підтримка процесу прийняття інвестиційних рішень для розвитку підприємства - Москаленко, Валентина Владимировна; Воловщиков, Валерій Юрійович; Гаращук, Кіра Андріївна (Eastern-European Journal of Enterprise Technologies, 2009)
This article represents general features of the development task of the business. The improved algorithm of building of development trajectory of business has been proposed as a base for the decision support system of the investment tasks. The concept of the decision support system of the investment tasks was proposed in this article.